PENGARUH SUCCESSOR READINESS TERHADAP SUCCESSOR EFFECTIVENESS DENGAN FAMILY HARMONY AND TRUST IN SUCCESSOR SEBAGAI VARIABEL MODERASI PADA BISNIS KELUARGA DI INDONESIA - Suhendra, Annisa; Padmalia, Metta (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
The succession process plays an essential role in securing the long-term operational continuity of family businesses. However, family businesses in Indonesia often face complex challenges related to succession. A common issue is the low effectiveness of successors in fulfilling their roles, which frequently becomes a key factor in succession failure. This suggests that not all family business successors are adequately competent or prepared to effectively lead the generational transition. The aim of this study is to examine the effects of successor readiness on successor effectiveness within the context of family businesses, while also considering the moderating role of family harmony and trust in the successor. Using a quantitative approach, data were gathered from 198 family business successors through questionnaires and analyzed using IBM SPSS Statistics 25 with the Moderated Regression Analysis (MRA) technique. The findings reveal that successor readiness has a positive and significant effect on successor effectiveness.